Calculate content of vitamin C in a pharmaceutical compound. PBL used as a strategy to make easy to learn chemistry at university. - López-Guerrero, María del Mar; Vereda-Alonso, Elisa Isabel; López Guerrero, Gema (My University, 2023)
In Project-Based Learning, teacher transmits to the students the contents that the curriculum marks, helping to motivate them and awaken their concerns about the previous knowledge. This way of working intends that students discover and feel that what they are learning in class has an application, in some cases close to their reality, it is not simple content that they must pass to pass the course. It is intended that they are aware that the learning they are doing is helping them to prepare for life. This work focuses on the utility of the laboratory as a space with a problem-solving approach, that is, contextualizing problems and fulfilling a series of purposes. These purposes are the ability to internalize general and specific knowledge (know), acquire technical and procedural skills (know how), develop attitudes (know how to be) and social skills (know how to live together). The laboratories allow the student to be trained, since the students are responsible for their own learning, thus contributing to their self-learning; Teamwork implies assertive communication, both in oral and written communication, which contributes to improving their skills. The students learned to discuss and support their ideas. Therefore, it was revealed that it is a training for the students, and it is managing to improve the performance of the students. The results have shown, after the students completed a questionnaire, after the laboratories, 59% of the students indicated that the experience contributed to their learning (aspects such as comprehension and self-learning) compared to 41% who thought that it did not help in this regard; 88% indicated that it helped them better understand the experience they were carrying out and only 14% stressed that there was no coherence between theory and practice.
Keywords: Química - Estudio y enseñanza superior; PBL; Gamification; Chemistry; Project-Based Learning